Perencanaan Ulang Jembatan Jurug Jln.Ir.Sutami Dengan Sistem Balok Prategang Mengacu Pembebanan RSNI T-02-2005 - Listiyanto, Slamet, Ir.Abdul Rochman, MT (2017)
The purpose of final project is to know prestressed concrete bridge construction design rules which is right, so it needs calculation relats to the standard with bridge redesigning of Jln.Ir.Sutami, Solo, Central Java. The bridge is class 1 has span of 175 m with 4 girders spans on its pier. The rules are used for refrence is rule of SNI T-02-2005 and redesign guidliness of Bridge Management System (BMS) 1992 in determining loading standard for bridge construction. Construction mechanic analysis is used for finding inside force which happens with using SAP 2000 V 15 Program. The methematic calculation in finding fast and accurat result used "Microsoft Excel 2013"program. Wherease, drawing used "AutoCAD 2012" program and "Sketchup 2015"program. This redesign is got 46 meters of girder with 2,3 meters of girder profile and for 41 meters of girder is got 2,1 meters of profile, for tendon which is used to 46 meters of girder and 41 meters is got 5 tendons and 4 tendonson longitudinal girder. In calculation of longitudinal 46 meters of girder did loss of prestress of 16,525 % and on ll 41 metersof longitudina did 16,879 % of loss of prestress . Longitudinal to stress , deflection, limit moment and shear force On bridge abutmentto be main 6 parts are breast wall, back wall, corbel, wing wall, pile capand bore pile foundaiton, wherease for pier is devided becomes 5 parts are headstock, column pier, beam diapragma, pile cap and bore pile foundation. keywords :redesing, Jurug, prestressed concrete, bridge, borepile.